The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12517-021-08735-3
|View full text |Cite
|
Sign up to set email alerts
|

Introducing affordable and accessible physical covers to reduce evaporation from agricultural water reservoirs and pools (field study, statistics, and intelligent methods)

Abstract: Nowadays, a major part of the stored surface water resources is wasted by evaporation. By implementing low-cost methods to prevent water evaporation, it is possible to return this part of water to the agricultural, industrial, and drinking cycles. The present study aimed to evaluate the effect of polystyrene (compressed foam), pieces of wood, and synthetic beeswax cover with different surface coverage of 60%, 70%, and 80% in the standard Colorado Sunken evaporation pan on the evaporation rate. The materials us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Figure 10 compares the changes of the parameters received from Semnan meteorological station including minimum temperature (Celsius), maximum temperature (Celsius), maximum humidity (percentage), minimum humidity (percentage), sunlight hours, pressure (hectopascal) and wind speed (meters per second) on test days; it also shows the rate of evaporation from the CASEP and CSSEP (mm) (Ghazvinian et al, 2021). From the obtained results, it can be deduced that wind speed and temperature are at their lowest correlation with the ER.…”
Section: Casep Cssepmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10 compares the changes of the parameters received from Semnan meteorological station including minimum temperature (Celsius), maximum temperature (Celsius), maximum humidity (percentage), minimum humidity (percentage), sunlight hours, pressure (hectopascal) and wind speed (meters per second) on test days; it also shows the rate of evaporation from the CASEP and CSSEP (mm) (Ghazvinian et al, 2021). From the obtained results, it can be deduced that wind speed and temperature are at their lowest correlation with the ER.…”
Section: Casep Cssepmentioning
confidence: 99%
“…The results showed that the ER from the MDF-containing pan was 91% lower than that of the CSSEP. Ghazvinian et al (2021) went on to place various coatings such as polystyrene, wood, and synthetic honey wax on the CSSEP, where they measured the evaporation and compared the ER from the control pan with the pan containing the coatings. The results showed that the rate of evaporation in the pan containing polystyrene was less than the evaporation in other pans and the control pan.…”
Section: - Introductionmentioning
confidence: 99%